Narrative mobile video game-based cognitive training to enhance frontal function in patients with mild cognitive impairment - Yeseul Choi; Jae-Sung Lim; Hagyun Choi; Yong Hoe Ryu; Eunkyung Seong; Inseok Park; Dong Won Kang; Jae-Hong Lee; Dong-Wha Kang (Scientific Reports)
Abstract Although cognitive training has been proposed as a possible therapeutic modality for mild cognitive impairment (MCI), most serious games focus on specific tasks. This study aimed to investigate the feasibility and efficacy of narrative video game-based cognitive intervention for MCI. A four-week (± 1-week) mobile game intervention was given to 17 MCI participants (mean age (SD) = 72.8(4.75)). At baseline and post-intervention, the participants received neuropsychological tests and a depression scale. Frontal function was assessed using the Corsi block-tapping test, Color Word Stroop Test, Controlled Oral Word Association Test, Digit Symbol Coding, and Trail Making Test-Elderly’s Version; depression was assessed using the Geriatric Depression Scale. User’s compliance and gaming experience were also evaluated. MCI patients showed significant improvements in frontal function, particularly in Digit Symbol Coding (mean ± SD, 0.47 ± 0.49, p = 0.007) and phonemic fluency (mean ± SD, 0.39 ± 0.55, p = 0.024). Each frontal subtest’s mean z-score was increased (mean ± SD, 0.44 ± 0.38, p = 0.008). Block span and depression scale remained unchanged. High adherence rates (122.35%) and favorable feedback on the gaming experience indicated that the game intervention’s usability boosted patients’ motivation and engagement. Our findings demonstrate that narrative game-based cognitive intervention was not only beneficial but also enjoyable for elderly MCI.